ANALISIS PEMELIHARAAN ANGGOTA BARU AGAR TETAP BERTAHAN DALAM GEREJA MASEHI ADVENT HARI KETUJUH JEMAAT CIHAMPELAS BERDASARKAN KOLOSE 2:7 - Yusuf Tana; Milton T. Pardosi (Jurnal Koinonia, 2016)
In this study, the authors examined the causes of why the new members of seventhday Adventist church did not survive in the congregation at Cihampelas Bandungchurch based on Colossians 2: 7. This study focuses on four indicators namely:What is the message of Colossians 2:7; what is the main causes of new members didnot survive in the church; what is the reason of the new members survived in thechurch; and what is the message Colossians 2: 7 to maintain new members.Generally, the church aims to bring people who are not converted into the fellowshipof the believers. The Seventh-Day Adventist Church is a organization blessed byGod with many souls that joining in the church through baptism, but most of thepeople who just join in the church did not survive in the church until the end of theirlives.In order to be faithful members and retaining the faith and trust that has been ownedby the new members of the Apostle Paul urged members of the newly christened ithas: (1) The roots are strong and sturdy in Jesus, which means emptying oneself ofearthly things and be one with Jesus; (2) Has a built Faith in Jesus means to haveunity of a close relationship with Jesus; (3) Growing fast in the faith that has beentaught that meant stay focused on the truth that has been obtained and is not affectedby the false teachings that exist around them; (4) Has the abundant life withThanksgiving greeting that indicates that the person has grown in his faith.Based on the results of this research, conducted by the author then there are fourthings of the main cause why the new members did not survive in the church: a coldwelcome from members - old members and employees of the church; Lack ofstudying the Bible before being baptized; Temptation of old habits (such as smoking,drinking, etc.); and lack of visiting the new members who just being baptized by thepastor and church employees. And also based on the results of interviews with 15people who were no longer active in the church, there are 9 people who cannot go tochurch because they were working on the Sabbath. Based on the results of theresearch questionnaire then there are three things that the main cause of newmembers to survive in the church: a good motive of every member of the newlybaptized to seek the Truth; Friendly relations were familiar with the old members inthe church; Attention and affection on the show members of the old to the newmembers.After the authors look at thecauses, the author concluded that due to the newmembers did not survive in the church is therefore less mature in knowledge of realtruth. That’s why before a person accepts Jesus as his/her personal Savior, he need tobe guided as much as possible in order to know surely the Faith to the real JesusChrist. Old members also need to help the new members who joined in the growth oftheir faith so that they can grow well into adulthood in their newly acquired faith.